2014
DOI: 10.1371/journal.pone.0106559
|View full text |Cite
|
Sign up to set email alerts
|

An NMR Metabolomic Study on the Effect of Alendronate in Ovariectomized Mice

Abstract: Alendronate sodium (Fosamax) is most widely used for the prevention and treatment of osteoporosis. It is a type of anti-resorptive agent that reduces the risk of fractures by changing bone turnover and bone mineral density. We investigated the effect of Fosamax on a mouse model of osteoporosis. Twenty-seven female C57BL/6JNarl mice were divided into three groups: sham, ovariectomized (OVX) and OVX + Fosamax (Fosamax). After 23 weeks, bone density of femurs was analyzed using microcomputed tomography (micro-CT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
1
13
1
1
Order By: Relevance
“…The BMD values obtained from the μCT images of the mouse maxilla ranged from 0.83 g/cm 3 to 1.55 g/cm 3 , which were considerably larger than values of the previous data, which ranged from 0.12 g/ cm 3 to 1.00 g/cm 3 for the same strain of mice, C57BL/6J mice [27][28][29][30]. This might be partly attributed to the difference in the targeted bones, which could be a key factor determining the BMD values in mice [31].…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The BMD values obtained from the μCT images of the mouse maxilla ranged from 0.83 g/cm 3 to 1.55 g/cm 3 , which were considerably larger than values of the previous data, which ranged from 0.12 g/ cm 3 to 1.00 g/cm 3 for the same strain of mice, C57BL/6J mice [27][28][29][30]. This might be partly attributed to the difference in the targeted bones, which could be a key factor determining the BMD values in mice [31].…”
Section: Discussioncontrasting
confidence: 70%
“…This might be partly attributed to the difference in the targeted bones, which could be a key factor determining the BMD values in mice [31]. Spinal [29], tibia [28], and femoral bones [27,29,30] have been used in previous studies, while the maxillary bone was used in the present study. Technical factors, including the scanner type, voltage, and kernel [32], can also affect the magnitude of the CT numbers in μCT and quantitative computed tomography (QCT) images; thus, this could cause the large discrepancy in BMD values between the previous and present studies [8].…”
Section: Discussionmentioning
confidence: 99%
“…Alendronate sodium, a nitrogen-containing bisphosphonate, is widely used for the prevention and treatment of osteoporosis. Chen and coworkers revealed that alendronate had profound effects on the serum metabolites in the OVX mice with significantly higher concentrations of 3-hydroxybutyrate, taurine, allantoin, acetate, and ethanol, as well as lower concentration of aspartate, associated with energy metabolism [37]. Evidence for the protective role of strontium fructose 1,6-diphosphate (FDP-Sr) against bone loss is by stimulating bone formation and suppressing bone absorption [50].…”
Section: The Biomarkers and Their Potential Values In Osteoporosismentioning
confidence: 99%
“…Taurine supplementation has been shown to increase bone mineral density in rats [50,51]. Furthermore, the pulsed P. ferulae treated mice had higher serum taurine concentrations than mice treated with alendronate [52], suggesting the pulsed P. ferulae may induce higher concentrations of metabolites related to bone health [52]. Arginine is involved in the synthesis of substrates (polyamines and proline) that are implicated in collagen synthesis [50,53,54].…”
Section: Discussionmentioning
confidence: 99%